Beta-blockers in septic shock: a magnifying glass on the relation heart vessel - Mathieu, Calypso; Zieleskiewicz, Laurent; Leone, Marc (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Beta-blocker therapy is a promising treatment in patients with septic shock. During septic shock, catecholamine plasma concentrations are increased due to endogenous production. Despite this increase, exogenous supply remains useful in order to achieve an adequate perfusion pressure, leading to organ perfusion (1). However, the persistent elevation of catecholamine plasma concentrations was associated with increased mortality (2). Excessive adrenergic stimulation is harmful to the heart (3). In animal studies, esmolol, a selective beta-1-adrenergic blocker, improves cardiac contractility, stroke volume (SV) and vascular responsiveness to norepinephrine (4-6). In patients with septic shock who were initially stabilized, Morelli et al. showed that esmolol infusion reduced heart rate, increased SV and reduced norepinephrine requirements (7). In this seminal study, the use of esmolol resulted in an impressive decrease in mortality.